Model For Decision Making In Implementing Process Imrpovement - Low, Shye Nee (2014)
Industries, especially the manufacturing industry, must respond quickly and efficiently to customer needs and to be market competitive. In response to the advanced rapid changes in the market, the industries needed to continuously refine their operational processes to reduce waste in production department. Industri, terutama industri pembuatan, perlu bertindak balas dengan cepat dan berkesan dengan keperluan pelanggan dan menjadi pasaran yang kompetitif. Sebagai tindak balas kepada perubahan pesat maju di pasaran, industri diperlukan untuk terus memperbaiki proses operasi mereka untuk mengurangkan pembaziran di bahagian pengeluaran.